POTENSI LEARNING TRAJECTORY SISWA DALAM PERBANDINGAN TRIGONOMETRI DI SMA - Mutmainah, Heti Qodar; Sugiatno, Sugiatno; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The potention of students learning trajectory in comparison of trigonometry of X IPA students at SMAN 1 Pontianak were uneffective. This research was describe to the potention of students learning trajectory there was a new inovation in mathematics learning model using learning trajectory, and to increase mathematics learning effectiveness of learning trajectory towar the potention of student on learning goals, learning activity, and hypothetical learning trajectory . This research is in the form of a semi-descriptive qualitative that uses a single subject design. The research sample consisted of 6 student (10% of 40 student in a class) as the experimental group selected by participatory observation technique. Participatory observation technique test, interview guidelines, documentation, discussion group forum and triangulation/combination were used to collect data. Based on final pretest and posttest data analysis using directly to completion. This is indicated by the increasing potential of students' learning trajectory in trigonometric comparisons in senior high schools using learning trajectory successfully achieved through unit circles. Thus, the potention of students learning trajectory can build on mathematical conceptual understanding in trigonometric comparison material. Keywords: Learning Trajectory, Potention, Trigonometry, and Unite Circle.